O processo de titulação das comunidades quilombolas à luz do direito fundamental à memória: os casos de “Retiro” e “Linharinho” - Machado, Thiago Luiz D'agostin (2012)
This work seeks to comprehend the lawful obstacles on the way to implementing article 68 of theTemporary Constitutional Provisions Act, which can be brought about by land title processes, currently provided in Decree 4.887/2003. It used a dialetic methodology and employed as techniques literature review and document analysis of two land title cases. These cases are in regard to two traditional black communities located in the state of Espírito Santo: Retiro and Linharinho. Prior to investigation, it analyzes the fundamental right to memory implicit in the Constitution, by establishing the relation among memory, time and law. Memory is used as the linking element to demonstrate how Brazil has forgotten its traditional black communities for one hundred years. From abolition of slavery – when these communites stopped being persecuted – to the Constitution of 1988 there was no legal treatment whatsoever. The Constitution recognized these communites, primarily in the proviso quoted and ensued intese debates by clearly acknowledging the right to land of the “remaining members of the ancient runaway slave communities”. The enduring lawful silence remained after the Constitution was promulgated, since no legislation was approved to make the article effective, but only administrative decrees. Yet these latter have only appeared ten years after the Constitution, which attests a feature of these communities that has accompanied them throughout their existence: invisibility. This is an essential attribute keeping them on the other side of the abyssal line. Then, from this perspective, the work briefly analyzed the legal timeline and the causes of invisibility of the traditional black communities. Next, it summarized the two cases cited and conducted a thorough investigation on them, revealing as the main lawful obstacles to realizing the constitutional proviso: the inexistence of especific law regarding the issue and the arbitrary acting of the Judiciary.